Development and evaluation of a training module for people with lived experience of mental illness using social contact strategy for stigma reduction: A study protocol. - Gurucharan Bhaskar Mendon; Santosh Loganathan; Maya Semrau; Anish V Cherian (PLoS ONE)
Social contact strategy or social contact based anti-stigma intervention, where a person with lived experience (PWLE) of mental illness shares his/her lived experiences with the target group, has been found to be effective in reducing stigma and discrimination. A culturally appropriate social contact based anti-stigma intervention training module would be helpful in training PWLE. Since there is no culturally appropriate training module available in India, there is a need to develop a training module for PWLE of mental illness to deliver a social contact based anti-stigma intervention. Thus, the proposed mixed-methods study aims to develop and test the efficacy of a training module for PWLE of mental illness, using social contact strategy to reduce stigma and discrimination towards people with mental illness amongst undergraduate students. The proposed study will be carried out in three phases; Phase-I: formative work will be conducted using an explorative research design. After a formative and extensive literature review, the culturally appropriate training module will be developed and subsequently reviewed and validated by mental health experts and service users. Phase-II: PWLE of mental illness will be trained using the developed manual adopting a case series design. Phase-III: To test the efficacy of the training, a quasi-experimental research design will be used, in which the target group's knowledge, attitudes and behaviour towards mental illness will be assessed pre- and post and at three-month follow-up. Socio-demographic data will be analysed using descriptive statistics. Qualitative data (Phase-I and Phase-III) will be analysed through thematic analysis. Based on normality distribution, a parametric test like RMANOVA or an equivalent non parametric test will be adopted during phase III for efficacy testing. In addition, the outcomes amongst the PWLE, i.e., self-stigma and self-esteem, will be assessed and use of the training module will be analysed using thematic analysis.